A framework for setting land conservation priorities in the Sierra Nevada - Davis, F. W.; Costello, C. J.; Stoms, D. M.; Machado, E. A.; Metz, J. (Proceedings of the Sierra Nevada Science Symposium, 2004)
The California Legacy Project (CLP) mission is "to enable the State and its partners in conservation to develop and implement a strategic and inclusive approach to conserving and restoring California's lands and natural resources." Here we provide a brief overview of a framework that we developed to serve the dual purpose of helping decision makers to evaluate current opportunities (e.g., current proposal applications for State conservation funds) and to help planners develop longer term conservation strategies that highlight general areas, species and communities for more focused analysis and collaborative planning. Site prioritization depends on the resources the site contains, the threat to those resources, and the conservation cost of mitigating that threat. We illustrate our framework using relatively coarse, readily available data for the Sierra Nevada Bioregion. Preliminary results suggest that many of the private lands of the region contribute important conservation value for terrestrial biodiversity. However, inter-site disparities in degree of threat and in conservation costs make the conservation "bang for buck" especially high in a smaller number of sites.
Keywords: California Legacy Project marginal value conservation planning prioritization decision support system GIS